Association of RXR-Gamma Gene Variants with Familial Combined Hyperlipidemia: Genotype and Haplotype Analysis. (13th October 2013) - Sentinelli, Federica; Minicocci, Ilenia; Montali, Anna; Nanni, Luisa; Romeo, Stefano; Incani, Michela; Cavallo, M. Gisella; Lenzi, Andrea; Arca, Marcello; Baroni, Marco G.
Abstract : Background . Familial combined hyperlipidemia (FCHL), the most common genetic form of hyperlipdemia, is characterized by a strong familial clustering and by premature coronary heart disease. The FCHL locus has been mapped to human chromosome 1q21-q23. This region includes the retinoid X receptor gamma (RXRG), a nuclear factor member of the RXR superfamily, which plays important roles in lipid homeostasis. Objective . To investigate the possible role of the RXRG gene in the genetic susceptibility to FCHL. Methods . Variations in RXRG gene were searched by direct sequencing, and the identified SNPs were genotyped by PCR-RFLP in 192 FCHL individuals from 74 families and in 119 controls. Results . We identified 5 polymorphisms in the RXRG gene (rs1128977, rs2651860, rs2134095, rs283696, and rs10918169). Genotyping showed that the A-allele of rs283696 SNP was significantly associated with FCHL (corrected P, P c < 0.01 ). Also the alleles of the rs10918169 and of the rs2651860 SNP were more frequent in FCHL subjects compared to those in controls, although not significantly after correction. When the clinical characteristics of the FCHL subjects were stratified by allele carrier status for each SNP, the rs2651860 SNP was significantly associated with increased levels of LDL-cholesterol and of Apo-B in T-allele carriers ( P < 0.04 ) . Finally, haplotypes analysis with all 5 SNPs confirmed the significant association of RXRG gene with FCHL. Specifically, the haplotype containing all 3 "at-risk" alleles, significantly associated with FCHL (A-allele of rs283696, G-allele of rs10918169, and T-allele of rs2651860), showed an OR (Odds Ratio) of 2.02, P c < 0.048 . Conversely, the haplotype without all these 3 alleles was associated with a reduced risk for FCHL (OR = 0.39, P c < 0.023 ). The "at-risk" haplotype CTTAG was also associated with higher LDL-C ( P < 0.015 ) . In conclusion, variation in the RXRG gene may contribute to the genetic dyslipidemia in FCHL subjects.